MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT PENGGUNAAN TEAM ACHIEVEMENT DIVISION UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Dwi Suharadita (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding concepts of mathematics is one of cogn itive competences that student have to ownin learningmathematics. Studentswere expected to do some activities to build their knowledge. Students would understand the topicif they done so. In fact, students’ competences on understanding concepts of mathematics and activities in learningprocess are still low. One of efforts to overcome this problem is usingStudent Team Achievement Division (STAD) typeof cooperative learning model. Purpose of research is to describe students’ understanding of mathematical conceptsandlearning activities using STAD type of cooperative learning model and conventional learning. This research was aquasi experiment with static group design which applied to VIII.5 class as experiment class and VIII.6 class as controlclass. Based on data analysis, it can be concluded that students’ understanding of mathematical conceptsusing STADtype of cooperative learning model is better than conventional learning and STAD type of cooperative learning modelalso give a good impact to increase learning activites of students.Keywords–cooperative learning,learning activities, STAD, understanding of mathematical concept